Radio dla zagranicy – od hard power do soft power w międzynarodowej nadawczości radiowej - Wielopolska-Szymura, Mirosława (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2017)
Shortly after its invention, radio began to be used for political broadcasting with an international range. It was used to exercise power at a distance, sending messages to overseas diplomatic outposts or colonial territories. In the inter-war period it became an instrument of propaganda, and during the II World War the countries engaged in the conflict began to broadcast propaganda to listeners abroad, trying to bring them to their way of thinking. Simultaneously, you could observe a change in the approach to the international use of radio. It was regarded that radio programmes didn’t have to be used for disinformation and manipulating foreign listeners, but that it could aid in building a positive image of a given country, by basing the messages on genuine information and presenting the country’s cultural attractions, as well as cultivating a positive opinion among among listeners abroad. In consequence the stations and programmes that emerged and which utilised soft power – in international communications, which was the impulse behind the development of a new public diplomacy treating the recipient of the message – the overseas public – as the object of the communicative process.